Development of high‐resolution YAP(Ce) x‐ray camera for the imaging of astatine‐211(At‐211) in small animals. Issue 11 (22nd September 2020) - Nakanishi, Kouhei; Yamamoto, Seiichi; Watabe, Tadashi; Kaneda‐Nakashima, Kazuko; Shirakami, Yoshifumi; Ooe, Kazuhiro; Toyoshima, Atsushi; Shinohara, Atsushi; Teramoto, Takahiro; Hatazawa, Jun; Kamada, Kei; Yoshikawa, Akira
Abstract : Purpose: Astatine‐211 (At‐211) is a promising alpha emitter for radionuclide therapy. High‐resolution in vivo imaging of At‐211 in small animals is needed for the development of At‐211 radiopharmaceuticals. For this purpose, we developed a low‐energy x‐ray camera using a thin YAlO3 :Ce (YAP(Ce)) plate to image the low‐energy x rays (73–87 keV) from the daughter radionuclide of At‐211 (Po‐211). Method: We optically coupled a 38 × 38 × 1‐mm YAP (Ce) plate to a position‐sensitive photomultiplier (PSPMT) to develop an imaging detector. A pinhole or a parallel hole collimator was attached to the imaging detector, and the performance was measured for 60‐keV gamma photons. With the developed x‐ray camera, we carried out imaging of a mouse that had been administered At‐211‐NaAt. Results: The intrinsic spatial resolution of the YAP (Ce) x‐ray camera was approximately 1.2 mm FWHM, and the energy resolution was 22% FWHM. With a 5‐mm‐thick parallel hole collimator, the spatial resolution was 3.8 mm FWHM with a sensitivity of 8 × 10 −4 at 10 mm, which is a typical distance from the surface of the collimator to a subject in mouse imaging. Using a 1‐mm diameter pinhole collimator, the spatial resolution was 1.8 mm FWHM with a sensitivity of 3.5 × 10 −4 at 10 mm from the collimator. In the mouse images measured by the developed x‐ray camera, we could clearly observe that the At‐211 accumulated in the thyroid gland and the stomach of the mouse. Conclusion: We concluded that the YAP (Ce) x‐ray camera is useful for  in vivo imaging of At‐211.